Root growth of corn seedlings as affected by soil resistance to penetration - Rosolem, Ciro Antonio; Fernandez, Elena Mercedes; Andreotti, Marcelo; Crusciol, Carlos Alexandre CostA (Pesquisa Agropecuaria Brasileira, 1999)
The soil resistance to penetration is affected by soil texture, compaction and moisture content. In this paper, the effects of the interaction of these factors on corn root growth was studied. Soil materials with 22, 30, 34, 41 and 48% of clay were packed in PVC tubes 10 cm high, with 4.3 cm of internal diameter to reach bulk densities of 1.07, 1.18, 1.36 and 1.53 g cm-3. Water was added to reach water potentials of -0.034, -0.106 and -0.640 MPa. Corn seedlings were grown in the tubes for 48 hours. When the soil bulk density was low, root growth was affected mainly by soil texture. As soil bulk density increased, there was a decrease in the effect of soil texture on root growth. The increase in soil strength caused a decrease in root length and in the number of seminal adventitious roots. The primary roots showed a lower penetration ability when compared to seminal adventitious roots. A soil resitance of 1.3 MPa caused a 50% decrease in seminal adventitious corn roots.